Improving Management of Municipal Solid Waste in India : Overview and Challenges - Hanrahan, David (World Bank, Washington, DC, 2014)
This study summarizes the findings of a non-lending analytical activity carried out by the World Bank in 2004 and 2005. The work was driven by concern over the quality of the urban environment, and undertaken in a context of uncertainty on the suitability and effectiveness of Bank investment in this area, particularly in regard to components that generate little or no direct revenue, like waste disposal and sewage treatment. The immediate objectives involved addressing specific problems established in consultation with clients, and identifying obstacles and challenges to the improved management of municipal solid waste (MSW) in Indian cities. The broader long-term objective of this work is to support municipal authorities in improving the quality of the urban environment within their jurisdictions, with the aim of achieving related public health and economic benefits.